An Anthropolinguistic Perspective to Ịgọ Ọjị (kola nut invocation) among the Igbo People of Nigeria - Oyeka, Chiamaka Ngozi (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2456, 2026)
One of the outstanding features that mark Igbo culture is the kola nut. In the traditional mould, the kola nut goes through a noticeable ritual termed igo oji or the kola nut invocation before it is eaten. Research have been carried out by Igbo scholars on the kola nut custom, especially in relation to its use and typology, but inadequate attention has been paid to the invocation. Hinged on the standard form of the kola nut invocation process, the present study therefore examines the invocation process with a view to delineating the nature of the invocation, the structure of the invocation and the manner of language used in the invocation in contemporary times. Twelve male adults were interviewed for this study. The choice of only males is based on the fact that in patriarchal Igbo society, kola nut is actually the business of men and so men are the custodians and repositories of knowledge about the kola nut. The researcher equally observed the custom of igo oji in three different occasions. Information gathered from the interviewees and the observations made, formed the data for this study.  Analysis of data shows that, in general, the process of igo oji is no longer strictly adhered to due to reasons of changes in religious inclination and orientation among the Igbo. Christian religion which most Igbo embraced is the major reason behind the shift in the traditional procedure for kola nut invocation. The three-pronged structure of the invocation is no longer followed, and the language of invocation has fallen from the poetic to the prosaic, with all the adverse implications to Igbo language. It is recommended that, to avoid conflict and disputations, Christians should restrict themselves to ekpere oji (prayers over kola nut) while traditionalists should continue with igo oji (kola nut invocation) Keywords: Kolanut, Ọjị Igbo, Culture, Religion, Lobes